Lower-Bound Solution of Foundation-Bearing Capacity under Circular Uniformly Distributed Load - Fang Wei; Wang Jiao; Zhang Wan-dongxing; Shi Li-jun (Advances in Civil Engineering, 2020)
The semispatial static allowable stress field was constructed by three-dimensional stress columns, and the analytical lower-bound solution of bearing capacity of Mohr–Coulomb foundation beneath circular uniformly distributed load was put forward for the first time. The influence of the amount of stress columns and soil shear strength parameters on the lower-bound solution of the foundation-bearing capacity is analyzed. The research showed that (1) when the number of stress columns is more than 9 (n > 4) and the friction angle is less than 30°, the relative error between the lower-bound solution of the bearing capacity and exact solution is less than 6.6%, (2) the suggested analytical solution is applicable for common clayey materials; thus, the application scope of the analytical lower-bound solution is further expanded, and (3) the influence of cohesion on bearing capacity is linear. However, with the increase of the friction angle, the bearing capacity increases faster and faster under all cohesion levels. The correctness and effectiveness of the proposed method were verified by literature comparison.